Visual Language – Let the Product Say What You Want - Wang, Jiaying; Hao, Shuailing; Shan, Jing; Song, Xiaoxu (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Visual Language is a multitasking on-line system focusing on e-commerce, which involves in generating accurate product descriptions for sellers and providing convenient product retrieval service for customers. To achieve this goal, the system adopts image description technology and multi-modal retrieval technology. By utilizing cross-modal generation technique, we could help sellers on rapid uploading products and customers on rapid retrieval, which could improve the experience of both sellers and customers.